Concomitant irradiation to checkpoint inhibitor therapy of hepatocellular carcinoma patients: a systematic retrospective, single-center analysis - Munker, Stefan; Roessler, Daniel; Öcal, Osman; Ben-Khaled, Najib; Bernhart, Kathrin; Ye, Liangtao; Piseddu, Ignazio; Vielhauer, Jakob; Reiter, Florian P.; Rodriguez, Isaac; Ricke, Jens; Teufel, Andreas; et al. (Oncology research and treatment, 2023)
Introduction: Immunotherapy has been established as the standard treatment option for patients with advanced hepatocellular carcinoma (aHCC). Despite the increased efficacy, disease progression occurs in a relevant proportion of patients even after an objective response. Combination concepts with locoregional therapy are currently under investigation for hepatic disease but are also in discussion for the control of distant metastasis. Radiotherapy is a highly effective treatment modality for local tumor control. It is also thought to increase the efficacy of checkpoint inhibition and sensitize distant lesions to the effects of immunotherapy, but may potentially increase adverse effects. In our center, few patients with aHCC treated with immune checkpoint inhibitors (ICIs) received concomitant radiotherapy for symptom or disease control. The aim of this study was to retrospectively analyze adverse effects and efficacy of concomitant radiotherapy in patients with aHCC treated with checkpoint inhibition. Methods: To this aim, patients who received a combination of ICI and radiotherapy in our institution were retrospectively considered for analysis. The predefined inclusion criterion was radiotherapy after initiated checkpoint inhibition and continuation of ICI therapy for at least 8 weeks. Adverse effects and efficacy measurements were performed according to local standards. Results: The database search of 2016-2021 revealed six consecutive patients fulfilling the predefined criteria for concomitant ICI and radiotherapy. Three patients received high-dose-rate brachytherapy (15 Gy) to treat progredient hepatic lesions. Two patients received stereotactic body radiotherapy (SBRT) (25-30 Gy) for symptom control, and 1 patient received brachytherapy and SBRT to treat metastases. No severe adverse events were reported in the period (<6 months) after concomitant radiotherapy. In 5 out of 6 cases, long-term tumor control could be achieved by this therapeutic combination. Conclusion: A good efficacy of concomitant radiotherapy and checkpoint inhibition has been achieved with no safety concerns. Further investigations should evaluate the safety, appropriate clinical context, and efficacy of this promising approach.